Assessment and Diagnosis of Mental Illness in EDs Among Individuals Without a Home: Findings from the National Hospital Ambulatory Care Survey - Hijab Ahmed (eScholarship Publishing, University of California, 2021)
Introduction: Homeless individuals lack resources for primary healthcare and as a result use the emergency department (ED) as a social safety net. Our primary objective in this study was to identify the differences between features of visits to United States (US) EDs made by patients without a home and patients who live in a private residence presenting with mental health symptoms or no mental health symptoms at triage. Methods: Data for this study come from the 2009–2017 National Health and Ambulatory Medical Care Survey, a nationally representative cross-sectional survey of ED visits in the US. We examined differences in waiting time, length of visit, and triage score among homeless patients, and privately housed and nursing home residents. We used logistic regression to determine the odds of receiving a mental health diagnosis. Residence, age, gender, race, urgency, and whether the person was seen in the ED in the previous 72 hours were controlled. Results: Homeless individuals made up less than 1% of all ED visits during this period. Of these visits, 47.2% resulted in a mental health diagnosis compared to those who live in a private residence. Adjusting for age, race, gender, triage score, and whether the person had been seen in the prior 72 hours, homeless individuals were still six times more likely to receive a mental health diagnosis despite reporting no mental health symptoms compared to individuals who lived in a private residence. Homeless individuals reporting mental health symptoms were two times more likely to receive a mental health diagnosis compared to privately housed and nursing home residents. Conclusions: Homeless individuals are more likely to receive a mental health diagnosis in the ED whether or not they present with mental health symptoms at triage. This study suggests that homelessness as a status impacts how these individuals receive care in the ED. Community coordination is needed to expand treatment options for individuals experiencing emergent mental health symptoms.